INDONESIA'S ECONOMIC DIPLOMACY IN INDONESIA-EFTA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IE-CEPA) - Santoso, Rizal Budi; Moenardy, Dwi Fauziansyah (Indonesian Association for International Relations, 2023)
This article aims to analyze Indonesia's economic diplomacy in the Indonesia-EFTA Comprehensive Economic Partnership Agreement (IE-CEPA), which can provide excellent opportunities for Indonesia to increase trade and investment with EFTA countries. The analytical framework used in this article is economic diplomacy with the operationalization of trade diplomacy, according to Okano-Heijmans. The research method in this article uses qualitative methods. The results of this article show that Indonesia's economic diplomacy gives a positive view of IE-CEPA as an important agreement to strengthen economic relations between Indonesia and EFTA countries through reducing import duty rates, eliminating non-tariff barriers, and protecting investment, which is expected to increase the power of competitiveness of Indonesian products in the European market and increase Indonesia's exports to EFTA countries.